The impact of airline franchising on air service provision in the Highlands and Islands of Scotland - Pagliari, Romano (Elsevier, 2003)
The aim of this paper is to evaluate the impact of airline franchising on levels of air service provision in the Highlands and Islands of Scotland. Results showed that while air carriers operating under franchise agreements were offering reduced levels of capacity, they were able, assisted by a more suitable mix of aircraft, to deliver significant service improvements. These improvements were manifested in the scheduling of more convenient flight times, a higher proportion of direct services and the introduction of new routes. Compared to the previous incumbent, franchised operators were also better able at managing capacity in relation to demand with increased load factors reported after 1993. The implications of these results is that little evidence could be identified of any substantial deterioration in service levels as a consequence of franchising.